Principali Commenti Medievali alla Messa Romana nei Secoli XII e XIII: Autori e Tipologia - Celiński, Łukasz (Warszawskie Studia Teologiczne, 2024)
In the 12th and 13th centuries, medieval commentaries on the liturgy reached the highest point of their development. Despite the passage of time, these writings still enjoy a certain interest today. On the one hand, they bear witness to the dynamism of the development not only of the liturgy itself, but also of the method of its interpretation. On the other hand, the medieval commentaries testify to the desire, present in some way in every age, to preserve what is valid, even if dated. This paper offers a concise look at the main medieval commentaries on the liturgy between the 12th and 13th centuries, containing descriptions of the rite of Mass. The main purpose is to offer the reader some basic information about their authors and the context of their emergence in order to better understand their content.